GEOCHEMICAL CHARACTERISTICS OF METAMORPHOSED HIGH K/Na DYKES IN EASTERN QUEEN MAUD LAND, ANTARCTICA : ULTRAPOTASSIC IGNEOUS ACTIVITY LINKED TO PAN-AFRICAN OROGENY - アリマ, マコト; シライシ, カズユキ; ARIMA, Makoto; SHIRAISHI, Kazuyuki (National Institute of Polar Research, 1993)
P(論文) Major and trace element abundances and mineralogy of exceptionally potassium-rich metamorphosed dyke rocks are described from Cambrian metamorphic terrains of eastern Queen Maud Land. They are characterized by extremely high K_2O, P_2O_5,Rb, Ba, Sr, Zr, and light rare earth elements. Although the dyke rocks have been metamorphosed to amphibolite facies grade, the geochemical characteristics collectively indicate that their precursors were ultrapotassic mafic igneous rocks of minette or lamproite affinity. The dykes are interpreted as a manifestation of post orogenic ultrapotassic igneous activity linked to the Pan-African orogeny. departmental bulletin paper